Free Radical Scavenging Activity of Chromolaena odorata L. Leaves - Putri Anni Maulida; Devi Anggraini Putri; Sri Fatmawati (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2019)
Chromolaena odorata is one of the plants used by the community as traditional medicine. Some of community in Ambon, Indonesia used C. odorata leaves as wound medicine. This study aims to evaluate free radical scavenging activity from fraction of methanol extract of C. odorata. Methanol extract of C. odorata leaves is known have good free radical scavenging activity. The fractionation from methanol extract of the C. odorata leaves obtained A-E fraction, where fractions C, D and E showed inhibitory activity against DPPH radicals (2,2-difenill-1-pikrilhidrazil) with IC50 values 63,95; 64.38 and 202.15 μg/mL. Positive control, which is gallic acid, has an IC50 value of 5.29 μg/mL.